Avaliação prospectiva de parâmetros de saúde em portadores do HIV mediante consulta de enfermagem - Carvalho, Carolina Maria de Lima (2010)
Nursing consultations identify HIV patients’ specific needs and enhances survival when the infection cannot be cured. The goal was to assess health parameters used during the nursing consultation, according to Orem’s Model, involving HIV patients. Clinical, intentional, prospective, concurrent longitudinal research. Participants were 30 HIV patients at a specialized outpatient clinic in Fortaleza-CE. Between November 2008 and August 2009, data were collected during the nursing consultation, using specific health instruments: quality of life (HAT-QoL), social support (Social Support Scale for People Living with HIV/aids), anxiety and depression (HAD), Adherence to antiretrovirals (CEAT-VIH). Each patient was exposed to six nursing consultations, at minimum intervals of 30 days, applying the different assessment instruments during the first and sixth consultation. Student’s t and Snedecor’s F test were used for data assessment, 2, Fisher-Freeman-Halton and Spearman’s linear correlation coefficient rs and Pearson’s r were used to assess association and correlation, with significance set at 5%. Twenty-one participants were men and nine women, between 22 and 62 years of age, and 23 took antiretroviral drugs. Regarding quality of life, significant changes (p<0.001) were observed after the nursing interventions, whose patients demonstrated better ratios in terms of: general and sexual activities, concerns with secrecy, financial concerns, awareness on HIV, satisfaction with life, medication-related issues and trust in the physician. As for social support, the variables indicated a significant improvement in emotional (p=0.005) and instrumental (p=0.013) support levels at the end of the study. Anxiety and depression levels were low and significant after the interventions, with p=0.001 and p=0.006, respectively. The comparison between adherence levels to antiretrovirals during the first and last intervention showed a significant difference (p=0.039), indicating improvements in medication use. The data show that patients’ coping with the disease improved, as well as the recovery process of health levels and reintegration into the family and social environment, and also upon returning to daily activities, thus permitting better adaptation to the illness, a better quality of life, greater social involvement, decreased anxiety and depression levels, besides treatment adherence. In conclusion, health monitoring of HIV patients, using nursing consultations focusing on self-care, may have supported the changes observed during the outpatient monitoring interval. This study revealed the urgent need for nurses to set up systematic outpatient follow-up for HIV patients in specialized health services, with a view to improving and promoting these clients’ health.